NFIB-Mediated lncRNA PVT1 Aggravates Laryngeal Squamous Cell Carcinoma Progression via the miR-1301-3p/MBNL1 Axis - Tian Tang; Feng Zeng (Journal of Immunology Research)
Laryngeal squamous cell carcinoma (LSCC) is one of the most common malignant tumors of head and neck cancers. In the past decades, although the therapy strategies of LSCC have made considerable improvement, the terrible outcomes of LSCC still bring an enormous burden to the world health care system. Novel therapeutic targets for LSCC are urgently needed. lncRNAs exert important roles in various biological progressions, including LSCC. Here, we aimed to investigate the function of lncRNA PVT1 in LSCC progression and its underlying molecular mechanisms. By conducting multiple experiments, our results showed that lncRNA PVT1 was upregulated in LSCC cell lines and regulated LSCC cell proliferation, apoptosis, and its cell susceptibility to natural killer (NK) cells. Moreover, it was found that lncRNA PVT1 promotes MBNL1 expression to regulate LSCC cellular progression through sponging miR-1301-3p. Our study might provide novel targets for LSCC basic research or clinical management.